Sistem Pendukung Keputusan untuk Menentukan Lahan Budidaya Tanaman Obat Keluarga (TOGA) menggunakan Metode Fuzzy-Gap Kompetensi - Yusuf Fadlila Rachman; Akhmad Syarif; Kusrini (Institut Shanti Bhuana, 2021)
TOGA or family medicinal plants is one of the plants that can generate personal benefits and mutual benefits. Determination of land is generally necessary because it can help users to be able to plant crops suitable for their land so that they can avoid losses. The purpose of this research is to build a decision support system to assist cultivators in determining the best land for cultivating TOGA. In this study, 5 types of medicinal plants were used, namely ginger, cardamom, turmeric, ginger, and kencur. The criteria used in this study, namely land distance, land conditions, and climatic conditions. The method used in this research is the competency fuzzy-gap. Each criterion chosen by the user will be converted into a fuzzy value, namely 0-1 by using an upward linear function for the benefit criteria and a downward linear function for the cost criterion. The fuzzy values ​​that have been obtained are used in calculations using the competency gap. The test results on manual calculations and in the program obtained the same results as the output of Land 1 is the best land with a value of 7.39625.